The Effect of Career Path and Worklife Balance on Intention to Resign with Gratitude as an Intervening Variable - Widowati, Mariatin Sri; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Research Objectives are analyze the effect of career path on resignation intention, analyze the effect of career path on gratitude, analyze the effect of work balance on resignation intention; analyze whether work balance affects gratitude, analyze the effect of gratitude on resignation intention. analyze the effect of career path on resignation intention through gratitude. Analyzing the effect of work balance on resignation intention through gratitude. Research Method is quantitative approach using Likert Scale. Data collection carried out through survey techniques questionnaire with a random sampling sample as much as 114 respondents. The results showed that career path has a significant effect on resignation intention. Career path has a significant effect on intention to resign. gratitude has a significant effect on resignation intention, career path has a significant effect on gratitude, work balance has a significant effect on gratitude, career path mediated by gratitude has a significant effect on resignation intention. Work balance mediated by gratitude has a significant effect on resignation intention